LEGAL PROTECTION OF CHILDREN AFFECTED BY INTERNATIONAL CHILD ABDUCTION: A COMPARATIVE ANALYSIS BETWEEN INDONESIA AND SINGAPORE - Sarah, Cut; Farsia, Lena (Universitas Syiah Kuala, 2025)
International child abduction remains a persistent issue in both Indonesia and Singapore. While Singapore has enacted specific regulations to address this matter through specific legislation, including the International Child Abduction Act 2010 (ICAA), Indonesia still lacks specific regulations explicitly governing international child abduction. This article analyzes the legal framework governing the protection of children affected by international child abduction, with a focus on relevant international legal instruments, and analyse a comparison of legal protections provided in Singapore and Indonesia. The study employs a normative legal research method, analysing primary legal material, such as international conventions and domestic laws, as well as secondary sources. A comparative approach highlights disparities between Indonesias and Singapores legal frameworks for addressing international child abduction. The finding shows that while the Hague Convention on the Civil Aspects of International Child Abduction 1980 (Hague Convention) and the Convention on the Rights of the Child (CRC) offer a robust framework, Singapore, through the ICAA, effectively enforces international standards. Conversely, Indonesia, such as Law No. 35 of 2014 and the Criminal Code, lacks a mechanism for cross-border resolution and often treats such cases as custody disputes. Countries should recognize and understand existing international instruments like the Hague Convention and CRC to establish clear mechanisms for addressing international child abduction. Indonesia should accede to the Hague Convention and integrate its provisions into its domestic laws, following Singapores structured approach to better address cross-border cases.